Halal Food: Research Mapping Related to Halal Food Using a Bibliometric Approach - Anastasya Dinda Syaputri (FEBI UIN Sunan Kalijaga, 2022)
The halal industry has enormous potential and is currently growing quite significantly in the world. As quoted from the Global Islamic Economy Report 2020/2021, one of the largest halal industries in Indonesia is Halal Food with total public consumption reaching US144 billion of the total global halal food consumption of US1.7 trillion and placing Indonesia in the first place. as the highest consumer of halal food. This research will try to map research related to the development of Halal Food research trends published by leading journals from 1990 to 2021 that have been indexed by Scopus, using the bibliometric method with the help of Vosviewer software. Based on the results of the analysis, research related to halal food shows an increase from year to year, with the highest number of publications on halal food coming from Malaysia, and the keywords most frequently used are halal, halal food, and article. Therefore it is hoped that research on halal food can be further developed using other methods such as biblioshiny